Analisis Fonotaktik Dalam Novel Baruang Ka Nu Ngarora - Salsabila, Shafa; Khotibah, Zaskia Nur; Ruiah, Ruiah; Syahputri, Dhaffina Marsha; Aldo, Hamzah; Juliana, Muhammad Ilham; Widyastuti, Temmy (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2026)
This study analyzes phonotactic aspects in the novel "Baruang Ka Nu Ngarora," a work of modern Sundanese literature. The focus of this study's analysis is the rules of vowel and consonant distribution, vowel and consonant clusters, clusters, diphthongs, and syllable structure. This study uses a descriptive qualitative method. Data was collected by reading the novel to identify phonotactic patterns in Sundanese words found in the novel. The data was described systematically in accordance with the principles of Sundanese phonotactics found in the book Ulikan Fonologi Basa Sunda (A Study of Sundanese Phonology). The results of the study show that the patterns of phoneme sequences in the novel, including the position of phonemes at the beginning, middle, and end of words, are as follows there are 7 vowel distributions, 16 consonant distributions, 15 consonant clusters, and 7 vowel clusters. clusters consisting of cl, cr, by, gr, bl, br, pl, pr, diphthongs divided into ascending and descending, and Sundanese syllable structure. This study reveals the linguistic characteristics of Sundanese in the context of modern literature and makes novels an important source of linguistic knowledge to strengthen the knowledge of Sundanese phonotactics in the process of language and literary advancement.